SPECIAL MEASURES’ APPLICATIONS FOR VICTIMS AND VULNERABLE AND INTIMIDATED WITNESSES IN MALAYSIA: NEW FRONTIERS TO RIGHT TO A FAIR TRIAL? (UUM Journal of Legal Studies, 2014)
Special treatment for victims and vulnerable and intimidated witnesses (VIWs) in a criminal process has developed over time in Western countries. The development of rights of victims’ and VIWs and awareness on their needs and interests in pre-trial process and court proceedings has initiated the use of special measures’ application. In England and Wales, some measures to lessen stress and trauma of such witnesses undergoing a criminal process were introduced into the legislations. Yet, as many other Asian countries, Malaysia developed her victims’ policy only in 1990s and issues relating to the protection of VIWs were raised within the criminal justice system just recently. The tendency to put the standpoint into practice in the Malaysian legal system is demonstrated in the establishment of the Evidence of Child Witness Act 2007 (ECWA 2007) and the amendment of Section 272B of the Criminal Procedure Code. On the other hand, it is also arguable that special measures’ applications for victims and VIWs will erode the right of defendants to a fair trial. This article aims at evaluating the current position of victims’ and VIWs’ rights and legal protection in the Malaysian criminal justice process. It elaborates on the rights of victims and other VIWs to special measures’ applications in pre-trial process and court proceedings. Special measures such as live TV-link, screens, removal of formal attire, intermediaries and visual aids communication are potential to accommodate victims’ and VIWs to give testimony in court. The use of video-recorded evidence is also evaluated as one of the means to facilitate traumatized victims and VIWs to give evidence and testimony. The possibility to enhance the use of special measures’ applications as one of the ways to advocate the right to a fair trial of victims and VIWs, without eroding the rights of the defendants, is also highlighted in this article.Keywords: Vulnerable, intimidated, special measures.